Simulation Game-Based Governance System Education - Glenn Hariyanto Putra; Erdhi Widyarto Nugroho; T.Brenda Chandrawati (Soegijapranata Catholic University, 2023)
Democratization is a process of people's participation in the country's political activities, but this process is quite difficult because the public's perception of the government tends to be negative. One way to increase public awareness about government is to use educational games such as